The Effect of Good Corporate Governance on Market Capitalization in Companies - Basith, Jundi Muhammad; Sundarta, M. Imam; Azis, Azolla Degita (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
This study aims to determine the effect of good corporate governance on market capitalization either partially or simultaneously, good corporate governance referred to here are audit committees, independent commissioners and institutional ownership. The population in this study uses food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. With a total sample of 13 companies. The sampling method in this study is based on the criteria of the population or also called purposive sampling. This research is a quantitative study that uses secondary data in the form of financial statements of manufacturing sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. In this study, we tested the panel data regression model using the chow test and selected the fixed effect model with generalized least squares to test the panel data regression. In this study, analysis was also carried out using descriptive analysis methods, classical assumption tests, T tests and F tests as well as analysis of the coefficient of determination R2. The results of research conducted partially show that the audit committee has no effect on market capitalization, then independent commissioners have a significant effect on market capitalization and institutional ownership has a significant effect on market capitalization. The results are carried out simultaneously indicating that the audit committee, independent commissioners and institutional ownership have a joint effect on market capitalization